Pengaruh Social Media Marketing terhadap Niat Beli Ulang melalui Trust sebagai Variabel Mediasi: Studi pada Pelanggan Produk Glad2Glow di TikTok Shop Kota Denpasar - I Kadek Nanda Devhana Radika; Wayan Santika (OPTIMAL Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the effect of social media marketing on repurchase intention through trust as a mediating variable among customers of Glad2Glow products on TikTok Shop in Denpasar City. The research is grounded in the Theory of Planned Behavior as the main theoretical framework. The study employed an associative quantitative approach with a sample of 120 respondents, consisting of Glad2Glow customers on TikTok Shop Denpasar. The sampling technique used was non-probability sampling with a purposive sampling method. Data were collected through questionnaires and analyzed using path analysis and the Sobel test. The findings indicate that social media marketing has a positive and significant effect on repurchase intention. Social media marketing also has a positive and significant effect on trust. Furthermore, trust itself has a positive and significant effect on repurchase intention. Trust is proven to positively and significantly mediate the effect of social media marketing on repurchase intention, indicating partial mediation. The practical implication highlights the importance for Glad2Glow to enhance transparency, consistency of product information, and commitment to customer satisfaction in their social media marketing strategy to build stronger trust and foster sustainable customer loyalty.